1986
DOI: 10.1002/cber.19861190820
|View full text |Cite
|
Sign up to set email alerts
|

Lichtinduzierte reversible Reaktionen: Synthesen und Eigenschaften photochromer 1,1‐Dicyan‐1,8a‐dihydroazulene und thermochromer 8‐(2,2‐Dicyanvinyl)heptafulvene

Abstract: t,l-Dicyan-2-aryl-l ,8a-dihydroazulene 6(a -g) werden ausgehend von 8-Methoxyheptafulven und Benzylidenmalonodinitrilen iiber Tetrahydroazulene 5 dargestellt. Die Dihydroazulene 6 lagern durch sichtbares Licht in 8-(2,2-Dicyan-l-arylvinyl)heptafulvene 7 um. Die Riickreaktion 7+6 erfolgt thermisch. Die chemische Stabilitat und damit die Zahl der reversiblen Cyclen des oszillierenden Gleichgewichts 6+7 hangt von den Substituenten der Arylreste ab. Die p-Methoxyverbindungen 6f, I f haben im Vergleich zu den p-Nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 39 publications
3
29
0
Order By: Relevance
“…The switching properties of 8 and its analogs, however, were not described. 16,17 The two different substituents on C-1 introduce a second stereocenter (C-1) in addition to C-8a, and in consequence diastereomeric mixtures of isomers can be formed. Recently, we have shown that DHA 1 can be used as chemodosimeter for thiols, producing a visible color change from orange to yellow that allows detection of sulfhydryl groups in solution.…”
Section: Reactivity and Functionalization Of The Five-membered Ring Omentioning
confidence: 99%
See 3 more Smart Citations
“…The switching properties of 8 and its analogs, however, were not described. 16,17 The two different substituents on C-1 introduce a second stereocenter (C-1) in addition to C-8a, and in consequence diastereomeric mixtures of isomers can be formed. Recently, we have shown that DHA 1 can be used as chemodosimeter for thiols, producing a visible color change from orange to yellow that allows detection of sulfhydryl groups in solution.…”
Section: Reactivity and Functionalization Of The Five-membered Ring Omentioning
confidence: 99%
“…Functionalization of position 2 on the DHA skeleton has been most extensively explored. 5,6,[9][10][11][12][13][14][15][16][17][22][23][24][25][26][27][28] Aromatic groups are the substituents most widely incorporated, but few examples with methyl group on C-2 or cyclopentyl between C-2/C-3 have also been reported. 22 As described in the introduction (Scheme 3), the syntheses have followed either: (i) the [8+2] cycloaddition protocol, (ii) the route via nucleophilic addition of acetophenones to tropylium, followed by a Knoevenagel condensation with malononitrile, or (iii) an initial Knoevenagel condensation followed by reaction with tropylium species.…”
Section: Reactivity and Functionalization Of The Five-membered Ring Omentioning
confidence: 99%
See 2 more Smart Citations
“…Raman spectroscopy has previously been used to monitor photoswitching of other photochromic systems and pericyclic ring-openings [17][18][19][20][21][22]. Infrared (IR) spectroscopy has also previously been used to investigate the DHA-X/VHF-X photochromic system in the solid state; however, for some of the compounds the IR absorbance was too weak to detect [23].…”
Section: Introductionmentioning
confidence: 99%